Sequencing Mirror-Image DNA Chemically. Issue 9 (20th September 2018) - Liu, Xianyu; Zhu, Ting F.
Summary: The development of mirror-image biology systems faces a crucial barrier of lacking an L-DNA sequencing technique. Here, we developed a practical method for sequencing mirror-image DNA by adopting the Maxam-Gilbert sequencing approach, through which specific nucleobases in an end-labeled L-DNA are cleaved by achiral chemicals. This technique may facilitate the therapeutic application of nuclease-resistant L-aptamer drugs, and bring the vision of building an alternative, mirror-image self-replicating system closer to reality. Graphical Abstract: Highlights: Developing a practical method for L-DNA sequencing Applying the classic Maxam-Gilbert sequencing method to mirror-image biology systems Sequencing nuclease-resistant L-DNA aptamers for therapeutic applications Abstract : A key technical hurdle in the development of mirror-image biology systems is the lack of a practical L-DNA sequencing approach. Liu and Zhu developed a method for sequencing mirror-image DNA by adopting the classic Maxam-Gilbert approach through cleavage of end-labeled L-DNA by achiral chemicals.